2022
DOI: 10.3390/rs14092253
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Agricultural Fields via DASFNet with Dual Attention Mechanism and Multi-scale Feature Fusion in South Xinjiang, China

Abstract: Agricultural fields are essential in providing human beings with paramount food and other materials. Quick and accurate identification of agricultural fields from the remote sensing images is a crucial task in digital and precision agriculture. Deep learning methods have the advantages of fast and accurate image segmentation, especially for extracting the agricultural fields from remote sensing images. This paper proposed a deep neural network with a dual attention mechanism and a multi-scale feature fusion (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Researches have shown that semantic segmentation methods have a better accuracy and robust prediction in high resolution satellite or aerial imagery [38][39][40][41][42]. Semantic segmentation models are applied and modified in farmland extraction [43][44][45][46][47], based on context representations, multi-scale or pyramid features, and attention modules. These networks have the benefits of enhancing [6] semantic representations by larger receptive fields and deeper networks.…”
Section: Introductionmentioning
confidence: 99%
“…Researches have shown that semantic segmentation methods have a better accuracy and robust prediction in high resolution satellite or aerial imagery [38][39][40][41][42]. Semantic segmentation models are applied and modified in farmland extraction [43][44][45][46][47], based on context representations, multi-scale or pyramid features, and attention modules. These networks have the benefits of enhancing [6] semantic representations by larger receptive fields and deeper networks.…”
Section: Introductionmentioning
confidence: 99%
“…Fox example, in medical image processing [ 1 , 2 ], semantic segmentation is utilized in tumor border extraction and organ/tissue measurement, which helps doctors to make scientific judgments quickly and efficiently. In agricultural fields [ 3 , 4 , 5 ], semantic segmentation of remote sensing images helps to map and monitor land use and land cover (LULC) changes for sustainable land development, planning, and management. In the autonomous driving system applications [ 6 , 7 ], vehicles need the semantic information of the surrounding scene to assist their understanding and perception of complex traffic situations.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2022) proposed a novel architecture called Coupled CNN and Transformer Network (CCTNet), which combines the local details of CNN and the global context of the transformer to achieve a 72.97% mIoU score on the Barley remote-sensing dataset. Lu et al (2022) proposed a deep neural network with Dual Attention and Scale Fusion (DASFNet) to extract farmland from GF-2 images of southern Xinjian. The result shows that the dual attention mechanism module can correct the shape and boundary of the fields effectively.…”
Section: Introductionmentioning
confidence: 99%